Hubungan Karakteristik Sosiodemografis Dengan Kejadian Depresi Pasca Persalinan Pada Ibu Nifas - Ambarwati, Eny Retna; Pratiwi, Kurniasari; , Agnes; , Istichomah; Sinta, Riadinata (Jurnal Kesehatan Madani Medika, 2025)
Background: Postpartum depression (PPD) is a common mental health problem among postpartum mothers that adversely affects the well-being of both mother and child. The prevalence of PPD in Indonesia is considerably higher than in many other developing countries. Sociodemographic factors play a crucial role as primary determinants of PPD. However, a local predictive model that simultaneously considers these variables is still lacking. Objective: To examine the association between sociodemographic characteristics (education, income, parity, pregnancy status, and age) and the occurrence of postpartum depression. Methods: This analytical observational study with a cross-sectional design was conducted among 84 postpartum mothers in Indonesia between August 2024 and July 2025. Samples were obtained using accidental sampling. Data were collected using the Edinburgh Postnatal Depression Scale (EPDS). The Chi-square test and bivariate logistic regression were employed for data analysis. Results: Husbands’ income below the regional minimum wage increased the risk of PPD by 13.5 times (95% CI: 3.6–50.7; p<0.001). Low educational level increased the risk by 3.5 times (95% CI: 1.2–10.2; p=0.024), primiparity by 2.7 times (95% CI: 1.0–7.1; p=0.046), and unplanned pregnancy by 10.1 times (95% CI: 2.8–36.4; p<0.001). Maternal age was not significantly associated with PPD (p=0.65). Conclusion: Sociodemographic factors such as low income, low educational attainment, and primiparity are key determinants of postpartum depression. Early detection and interventions targeting social risk factors are essential to reduce the prevalence of PPD.